Soil Quality Assessment in Relation to Food Crop Productivity to Support Agribusiness-Based of Dry Land Management by Scoring of Soil Quality - L M Rachman (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
To support Indonesian’s food self-sufficiency program, more quantitative and accurate data are required on the character of soil data needed, which can be more easily understood, practical and suitable for crop selection as well as for the right fertilizer recommendations to support the agribusiness development, implementation and operation. The purpose of this research is to develop and assess soil quality in relation to the productivity of major food crops by using Soil Quality Score Plus (SQS Plus) to support agribusiness-based management of dry lands. The use of SQS for assessing soil quality in principle determines the weighted average score obtained from the score of each selected key parameter multiplied by its weight. The SQS for the 36 locations observed varies from 2.36 (low) to 4.12 (high). SQS Plus adds letter(s) after a score to indicate the limiting factor(s) of soil ecosystem. The most limiting factor is low carbon organic content (72.2 % from the 36 locations observed), followed by low P availability (58.3%), and low total organic N (41.7%). Data of correlation between SQS and crop productivity is not good as expected. Crop growth and crop production are not only determined by soil quality and its limiting factors. Keywords: Crop productivity, dry land management, soil limiting factors, soil quality assessment, Soil Quality Score